Access to justice in environmental matters in Turkey: A case study from the ancient city of Allianoi. Issue 4 (December 2015) - Elvan, Osman Devrim; Turker, Y. Ozhan
Abstract: Access to justice in environmental matters is one of the three rights established by the Aarhus Convention, but because Turkey does not adhere to the convention, it is not regulated by municipal law. However, some national plans and strategies have been defined and a series of targets have been set. In the case study, the issue of access to justice was assessed for judicial procedure initiated against a dam project and the threat of destroying Allianoi, a culturally significant ancient city. The dam project was closely followed by the Turkish public. The assessment was carried out by applying the Access Initiative Method to the sample case. The data were controlled by a SWOT analysis based on the legislation and practice of access to justice. The study suggests that the basic qualities of access to justice in environmental matters in Turkey are sufficient, although there are some deficiencies.